High-resolution paired carbon isotopic records from the Meishucun section in South China: Implications for carbon cycling and environmental changes during the Ediacaran-Cambrian transition - Zhang, Xiaolin; Zhou, Xin; Hu, Dongping (Precambrian research, 2020)
•Close link between transgressions and negative δ13C excursions during the E-C transition.•Incursion of 13C-depleted anoxic/euxinic deep waters into shallow-water environment.•Ocean stratification and vertical δ13C gradients.•Reduction of vertical δ13C gradient reflects deep ocean ventilation and oxygenation.•Deep ocean oxygenation facilitated the radiation of metazoans during the Cambrian explosion. Several prominent negative carbon isotope (δ13C) excursions are observed during the Ediacaran-Cambrian (E-C) transition, reflecting large perturbations of the carbon cycle in the ocean–atmosphere system. These negative δ13C excursions have been linked to dramatic paleoenvironmental changes and been widely used as regional and global chemostratigraphic correlation tools. However, there is still much debate about their causes and mechanisms. In this study, we report high-resolution δ13C records of both carbonate (δ13Ccarb) and organic carbon (δ13Corg) from the Meishucun section in South China. Combined with lithological variations and intrabasinal correlations, we find that the negative δ13C excursions during the E-C transition in South China are tightly linked with transgressive events. The existence of a large vertical (surface-to-deep water) δ13C gradient in a stratified ocean, and episodic incursions of 13C-depleted anoxic/euxinic deep waters into shallow water environment through enhanced upwelling or shoaling of the chemocline, may have contributed to these negative δ13C excursions. In addition, our results also imply a large reduction in the vertical δ13Corg gradient during the E-C transition, which may reflect the ventilation and oxygenation of the deep ocean. The corresponding expansion of oxic seafloor conditions and a large increase in the extent of habitable space for animals may have facilitated the radiation of metazoans during the Cambrian explosion.